Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/pld3.29
|View full text |Cite
|
Sign up to set email alerts
|

A brittle‐2 transgene increases maize yield by acting in maternal tissues to increase seed number

Abstract: The enzyme ADP-glucose pyrophosphorylase is essential for starch biosynthesis and is highly regulated. Here, mutations that increased heat stability and interactions with allosteric effectors were incorporated into the small subunit of the isoform known to be expressed at high levels in the maize endosperm. The resulting variants were transformed into maize with expression targeted to the endosperm. Transgenes harboring the changes increased yield some 35%; however, yield enhancement occurred via an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 38 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…These observations are not consistent with the long‐held premise that the BT2 protein functions only in the endosperm and, there, only in the cytosol. Furthermore, recent studies with engineered SH2 and BT2 proteins (Hannah et al ., , ) show that these genes function in the plant to increase seed number. Although the SH2 and BT2 proteins do not contain transit peptides, and hence should be exclusively found in the cytosol, Hennen‐Bierwagen et al .…”
Section: Discussionmentioning
confidence: 99%
“…These observations are not consistent with the long‐held premise that the BT2 protein functions only in the endosperm and, there, only in the cytosol. Furthermore, recent studies with engineered SH2 and BT2 proteins (Hannah et al ., , ) show that these genes function in the plant to increase seed number. Although the SH2 and BT2 proteins do not contain transit peptides, and hence should be exclusively found in the cytosol, Hennen‐Bierwagen et al .…”
Section: Discussionmentioning
confidence: 99%
“…The expression of maize sh2 AGPase genes in maize (Hannah et al, 2012), rice (Smidansky et al, 2003), and wheat (Smidansky et al, 2002) increased crop yields by increasing the number of grains produced per plant. Analyses of the various GlgC and/or ZmBT1 transgenic plants cultured in growth chambers indicate no significant increases in total seed number or total number of panicles per plant (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression of BEI, AGPL1, and AGPS1, which are involved in storage starch production, was significantly induced in transgenic plants (Supplemental Table S4). AGPase is a key regulatory step in the starch biosynthesis pathway, and its activity strongly affects rice grain yield (Smidansky et al, 2002(Smidansky et al, , 2003Kawagoe et al, 2005;Li et al, 2011b;Hannah et al, 2012). BEI has a specific role in determining the amylopectin fine structure in rice endosperm (Satoh et al, 2003).…”
Section: Discussionmentioning
confidence: 99%